PENGARUH KEPERCAYAAN,KERAGAMAN PRODUK,DAN BRAND IMAGE TERHADAP KEPUTUSAN MENABUNG PADA BPR DANA CENTRAL MULIA BATAM - susan, susan; S.kom.,Msi., Heryenzus (LPPM Universitas Putera Batam, 2021)
Currently, the business environment moves very fast and is dynamic in a short period of time which results in intense competition, as well as maintaining loyal customers, one of which is BPR which is currently very rapidly spreading, resulting in very tight and challenging competition, one of which is competition in the diversity of savings products where every BPR have different savings products so that they can attract the attention of saving customers. However, the trust of a customer is very important for customers to keep saving in the long term As a financial institution that relies on public trust, customers' trust in the bank will influence customers in making decisions so that customers feel safe and comfortable during transactions in the banking world, and there are many competitors that influence each other, including trust, product diversity, brand image. This study aims to determine whether trust, product diversity and brand image influence the decision to save at BPR Dana Central Mulia The research design used with causality research related to the quantitative approach. The sample was determined using probability sampling of 150 respondents. Data collection using a questionnaire measured with a Likert scale. The data collected, analyzed with the SPSS version 21 program program obtained the results of t count confidence 17,739, product diversity 6,923, brand image 3,454 each sig zero compared to t table 1,97796 then t count> t table, for f test count 877,553> f table 3.06 concluded that trust, product diversity, brand image had a significant and simultaneous influence on nebaung decisions at BPR Dana Central Mulia Batam with determination research (R2) had an effect of 9.46%.